Estrogen Deficiency Exacerbates Type 1 Diabetes–Induced Bone TNF-α Expression and Osteoporosis in Female Mice - Raehtz, Sandi (Endocrinology, 2017)
Estrogen deficiency after menopause is associated with rapid bone loss, osteoporosis, and increased fracture risk. Type 1 diabetes (T1D), characterized by hypoinsulinemia and hyperglycemia, is also associated with bone loss and increased fracture risk. With better treatment options, T1D patients are living longer; therefore, the number of patients having both T1D and estrogen deficiency is increasing. Little is known about the mechanistic impact of T1D in conjunction with estrogen deficiency on bone physiology and density. To investigate this, 11-week-old mice were ovariectomized (OVX), and T1D was induced by multiple low-dose streptozotocin injection. Microcomputed tomographic analysis indicated a marked reduction in trabecular bone volume fraction (BVF) in T1D-OVX mice (~82%) that was far greater than the reductions (~50%) in BVF in either the OVX and T1D groups. Osteoblast markers, number, and activity were significantly decreased in T1D-OVX mice, to a greater extent than either T1D or OVX mice. Correspondingly, marrow adiposity was significantly increased in T1D-OVX mouse bone. Bone expression analyses revealed that tumor necrosis factor (TNF)–α levels were highest in T1D-OVX mice and correlated with bone loss, and osteoblast and osteocyte death. In vitro studies indicate that estrogen deficiency and high glucose enhance TNF-α expression in response to inflammatory signals. Taken together, T1D combined with estrogen deficiency has a major effect on bone inflammation, which contributes to suppressed bone formation and osteoporosis. Understanding the mechanisms/effects of estrogen deficiency in the presence of T1D on bone health is essential for fracture prevention in this patient population.